Visitors' Satisfaction Survey in Mudumalai and Indira Gandhi Wildlife Sanctuaries of Tamil Nadu - Sekar, T. (Indian Forester, 2002)
Nature tourism travel is emerging as the fastest growing segment in tourism accounting for nearly 20% of all international travel. Wilderness recreation has to ensure responsible travel and in the process , conserve environment and improve the well being of the local people so as to sustain the tourism potential in such locations. Though tourism is at present pursued in most of the Protected Areas only as an incidental activity , its role in support of management is increasingly being realized. As the visitor's satisfaction largely determines his willingness to remain in the tourism area for a longer duration or return to the area again , a questionnaire survey to assess the visitor's satisfaction was conducted in the two Protected Areas of Tamil Nadu viz. , at Theppakadu in Mudumalai and at Topslip in Indira Gandhi Wildlife Sanctuary among the tourists during May 2001.